Association between 19-bp Insertion/Deletion Polymorphism of Dopamine _-Hydroxylase and Autism Spectrum Disorder in Thai Patients - Wikrom Wongpaiboonwattana; Areerat Hnoonual; Pornprot Limprasert (My University, 2022)
Background and Objectives: Autism spectrum disorder (ASD) is a neurodevelopmental disorder the cause of which is not fully known. Genetic factors are believed to play a major role in the etiology of ASD. However, genetic factors have been identified in only some cases, and other causes remain to be identified. This study aimed to identify potential associations between ASD and the 19-bp insertion/deletion polymorphism in the dopamine beta-hydroxylase (DBH) gene which plays a crucial role in the metabolism of neurotransmitters. Materials and Methods: The 19-bp insertion/deletion polymorphism upstream of the DBH gene was analyzed for associations in 177 ASD patients and 250 healthy controls. Family-based analysis was performed in family trios of each patient using the transmission disequilibrium test to investigate the potential contributions of this DBH polymorphism to ASD. Results: The frequency of the 19-bp insertion allele was significantly higher in the patient group compared to the controls (0.624 vs. 0.556, respectively; p = 0.046). The frequency of the insertion/insertion genotype was also higher in the patient group (0.378 vs. 0.288, respectively) but without statistical significance (p = 0.110). The family-based analysis showed an association between patient families and the insertion allele when only families of male participants were analyzed (73 vs. 48 events; OR 1.521; 95% CI 1.057-2.189; p = 0.023). Conclusions: This population-based analysis found an association between the 19-bp insertion allele of the DBH gene and ASD. No association at the genotype level was found. The family-based analysis found an association between the insertion allele and ASD when the analysis was performed on male participants only, suggesting a linkage between the DBH locus and ASD.
Keywords: Transmission disequilibrium test; Genetic Association; Etiology; Insertion; Autism Spectrum Disorder Research